2020
DOI: 10.1016/j.jneuroim.2020.577294
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré syndrome in a patient infected with SARS-CoV-2, a case report

Abstract: Background: The COVID-19 is a novel condition affecting all the world, so every manifestation of disease should be reported. Neurologic manifestations of the disease are increasingly identified and this will help clinician to improve their diagnostic and therapeutic skills in dealing with COVID-19 patients. Case: In this article we report a 41-year-old male that developed ascending paresthesia and paralysis following infection with SARS-CoV-2 virus. Electrodiagnostic evaluation in patient revealed demyelinatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 13 publications
1
36
0
2
Order By: Relevance
“…In all (n = 72) but four patients [10,37,40,56], GBS manifestations developed after those of COVID-19 [median (IQR): 14 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), min 2-max 33 days]. Differently, COVID-19 symptoms began concurrent in one case [37], 1 day [40] and 8 days [55] after GBS onset in two other cases and never developed in another one [10] (Table 1).…”
Section: Clinical Features Of Gbs Spectrummentioning
confidence: 99%
“…In all (n = 72) but four patients [10,37,40,56], GBS manifestations developed after those of COVID-19 [median (IQR): 14 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), min 2-max 33 days]. Differently, COVID-19 symptoms began concurrent in one case [37], 1 day [40] and 8 days [55] after GBS onset in two other cases and never developed in another one [10] (Table 1).…”
Section: Clinical Features Of Gbs Spectrummentioning
confidence: 99%
“…Among the 68 studies on the CNS effects, 46 were case reports [16,17,, followed by 10 retrospective studies [64][65][66][67][68][69][70][71][72][73], 4 observational cohort studies [74][75][76][77], 3 prospective studies [78][79][80], 3 case-control studies [81][82][83] and 2 cross-sectional studies [84,85]. Among the 21 studies regarding PNS disorders, there were 19 case reports [86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104], 1 prospective study [78] and 1 retrospective study [68]. Two studies reported both CNS and PNS effects of COVID-19 [68,78].…”
Section: Categorization and Characteristics Of The Selected Studiesmentioning
confidence: 99%
“…As regards the PNS, the most frequent manifestations reported by literature were Guillain-Barré [78,87,88,90,93,[95][96][97][98][99][100][101][102]104] and Miller Fisher syndromes [89,91,94]. SARS-CoV-2 neuro-invasiveness is a complex process that probably depends on multiple interacting factors such as viral load, tissue neurotropism and host immune response.…”
Section: Effects Of Sars-cov-2 On Pnsmentioning
confidence: 99%
“…Among those existing medications used for COVID-19 are intravenous immunoglobulins (IVIG) which are known for their anti-in ammatory effects and approved in several immune mediated disorders, including Kawasaki syndrome. Such disorders have increasingly been reported also to COVID-19 [1][2][3][4][5]. Recently, two marketed IVIG products were shown to react with SARS-CoV 2 antigens in vitro [6].…”
Section: Introductionmentioning
confidence: 99%